Resveratrol as an Enhancer of Apoptosis in Cancer: A Mechanistic Review - Ashrafizadeh, Milad; Taeb, Shahram; Haghi-Aminjan, Hamed; Afrashi, Shima; Moloudi, Kave; Musa, Ahmed E.; Najafi, Masoud; Farhood, Bagher (Anti-Cancer Agents in Medicinal Chemistry, 2021)
The resistance to therapy of cancer cells is a challenge for achieving an appropriate therapeutic outcome. Cancer (stem) cells possess several mechanisms for increasing their survival following exposure to toxic agents such as chemotherapy drugs, radiation, as well as immunotherapy. Evidences show that apoptosis plays a key role in the response of cancer (stem) cells and their multi-drug resistance. Modulation of both intrinsic and extrinsic pathways of apoptosis can increase the efficiency of tumor response and amplify the therapeutic effects of radiotherapy, chemotherapy, targeted therapy, and also immunotherapy. To date, several agents, as adjuvant, have been proposed to overcome the resistance of cancer cells to apoptosis. Natural products are interesting because of the low toxicity on normal tissues. Resveratrol is a natural herbal agent that has shown interesting anti-cancer properties. It has been shown to kill cancer cells selectively while protecting normal cells. Resveratrol can augment reduction/oxidation (redox) reactions, thus increases the production of ceramide and the expression of apoptosis receptors, such as Fas Ligand (FasL). Resveratrol also triggers some pathways which induce the mitochondrial pathway of apoptosis. On the other hand, resveratrol has an inhibitory effect on antiapoptotic mediators, such as Nuclear Factor Κ B (NF-ΚB), Cyclooxygenase-2 (COX-2), Phosphatidylinositol 3– Kinase (PI3K), and mTOR. In this review, we explain the modulatory effects of resveratrol on apoptosis, which can augment the therapeutic efficiency of anti-cancer drugs or radiotherapy.
Keywords: cancer